IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA PENDIDIKAN INKLUSIF DI SD MUHAMMADIYAH 3 SURAKARTA - Lany Fitriati; Lina Ghorizah; Choiriyah Widyasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to describe the implementation of differentiated learning in inclusive education at SD Muhammadiyah 3 Surakarta, identify the obstacles faced by teachers, and analyze the school’s efforts in supporting inclusive education. The research used a qualitative approach with a descriptive design. The subjects of the study consisted of the principal, classroom teachers, and parents of students with special needs selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that differentiated learning was implemented through adjustments in content, process, and product according to students’ learning needs. Teachers simplified learning materials, used concrete and visual media, provided individual assistance, applied flexible grouping, and gave various forms of assignments. The implementation of differentiated learning increased students’ participation, confidence, and learning motivation. Several obstacles were still found, including limited teacher competence, the absence of special assistant teachers, limited adaptive learning media, and the lack of optimal individualized learning programs. The school demonstrated its commitment to inclusive education through initial assessments, curriculum adaptation, collaboration with parents, teacher training, and the development of differentiated learning tools and inclusive service programs.